2014
DOI: 10.1128/aem.03057-13
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus helveticus MIMLh5-Specific Antibodies for Detection of S-Layer Protein in Grana Padano Protected-Designation-of-Origin Cheese

Abstract: bSingle-chain variable-fragment antibodies (scFvs) have considerable potential in immunological detection and localization of bacterial surface structures. In this study, synthetic phage-displayed antibody libraries were used to select scFvs against immunologically active S-layer protein of Lactobacillus helveticus MIMLh5. After three rounds of panning, five relevant phage clones were obtained, of which four were specific for the S-layer protein of L. helveticus MIMLh5 and one was also capable of binding to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, evidence that both phagocytosis and constitutive macropinocytosis contributed to the uptake of strain NCFM was provided (18). Lack of stimulation of plasma membrane Toll-like receptors (TLRs) prior to endocytosis was also shown to be a prerequisite for strong IFN-␤/IL-12p70 induction (18) by L. acidophilus NCFM, whose S-layer protein shares a high level of similarity with that of L. helveticus MIMLh5 (73% identity and 83% positivity) (19).…”
mentioning
confidence: 99%
“…In addition, evidence that both phagocytosis and constitutive macropinocytosis contributed to the uptake of strain NCFM was provided (18). Lack of stimulation of plasma membrane Toll-like receptors (TLRs) prior to endocytosis was also shown to be a prerequisite for strong IFN-␤/IL-12p70 induction (18) by L. acidophilus NCFM, whose S-layer protein shares a high level of similarity with that of L. helveticus MIMLh5 (73% identity and 83% positivity) (19).…”
mentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) are more stable and reproducible and would be an attractive alternative for QC applications. A few studies reported the mAbs applied to LAB and probiotics, such as Stuknyte and colleagues who developed a mAb targeting L. helveticus SLP (from a different strain) for its detection in cheese by western blot (Stuknyte et al 2014). Another study also reported the development of anti-bifidobacteria mAbs used for immuno-culture methods (Amrouche et al 2006).…”
Section: Antibody Productionmentioning
confidence: 99%
“…The S-layer is built from one or more (glyco)-protein subunits, Slayer proteins (SLPs), that self-assemble into a highly exible and dynamic lattice through an entropy-driven process, allowing for structural adaptation in response to changing environmental conditions 4,[6][7][8][9][10] . So far, S-layers have been shown to serve various functions, including cell stability, adhesion, molecular sieve, and aiding in osmotic stress adaptation 6,[11][12][13] . Still, each S-layer's exact functionality and assembly properties remain unclear.…”
Section: Introductionmentioning
confidence: 99%